Preventing empirical antibiotic treatment failure in migrant populations: screening by infection risk, not ethnic background - Steven L. Taylor; Lito E. Papanicolas; Erin Flynn; Mark A. Boyd; Steve L. Wesselingh; Geraint B. Rogers (International Journal of Infectious Diseases, 2023)
Multidrug-resistant organisms (MDROs) are a major international health threat. In many low and middle-income countries poorly regulated antibiotic use, limited surveillance, and inadequate sanitation give rise to high rates of antibiotic resistance. A resulting reliance on last-line antibiotic options further contributes to the emergence of MDROs. The potential for these pathogens to spread across international borders is a matter of considerable concern. However, this problem is commonly framed as primarily a threat to the health security of countries where resistance is not yet endemic. In fact, it is little acknowledged that those at greatest risk from antibiotic treatment failure are individuals who move from regions of high MDRO prevalence to settings where standard empirical treatment options remain largely effective. In this perspective, we highlight the poor treatment outcomes for disseminated bacterial infections in individuals who have moved from settings in which MDROs are common to those where MDROs are currently less common. We discuss MDRO screening strategies that could avoid stigmatizing vulnerable populations by focusing on future risk of disseminated infection, rather than past risk of acquisition. In practical terms, this means screening individuals before childbirth, immunosuppressive treatments, major surgery, or other events associated with disseminated infection risk, rather than prioritizing screening for individuals from regions with high carriage rates. We argue that such measures would reduce antibiotic treatment failure and improve outcomes while protecting migrant populations from the divisive consequences of targeted screening programs.